AB0153 Deletion of receptor for advanced glycation end products (RAGE) does neither affect auto-antibody production nor development of renal disease in pristane-induced lupus. (15th June 2017) - Chevalier, N; Rzepka, R; Voll, R
Abstract : Background: Systemic lupus erythematosus (SLE) is characterized by autoantibodies to diverse autoantigens, especially to nuclear components such as double-stranded DNA (dsDNA) or nucleosomes. Still, it remains unclear why poorly immunogenic molecules such as dsDNA and nucleosomes become targets of humoral autoimmunity in SLE. Increased signaling via pattern-recognition receptors (PRRs) through pathogen-associated molecular patterns (PAMPs) or endogenous damage-associated molecular patterns (DAMPs) released from damaged or stressed host cells and tissues, may be critically involved in the break of tolerance against such nuclear antigens. One important PRR in this context may be RAGE. Among many others, RAGE recognizes High mobility group box 1 (HMGB1). HMGB1 is a DNA-binding nuclear protein that has been found at elevated levels in patients with SLE and other autoimmune diseases; likewise perpetuation of RAGE signaling sustains inflammation and leads to the establishment of chronic inflammatory disorders. Objectives: We therefore examined, using the Pristane-induced SLE model, if increased RAGE signaling may be involved in the break of tolerance against nuclear antigens and contributes to chronic inflammation. Methods: To that end, WT and RAGE-/- animals were injected intra-peritoneally with a single dose of pristane. Disease manifestations were determined after 7 months and included the determination of proteinuria and renal pathology by evaluating the glomerular cellularity and matrix on H&E stained paraffin-embedded kidney sections and glomerular depositions of IgG and C3c. In addition to that we checked for auto-antibody production at several time points during disease development and immune cell distribution, differentiation and phenotype in inflamed kidneys and spleen. Results: Apart from a slight decrease in GL7 hi Fas hi germinal center B cells and B220 + CD21 low CD23 hi follicular B cells in RAGE-/- animals, we did not detect differences in auto-antibody secretion or disease manifestations between RAGE-/- and WT mice. Conclusions: Our data contrast with recently published data showing that a deletion of RAGE exacerbated lupus nephritis and lymphoproliferation in a different SLE model (B6-MRL Fas lpr/j). Therefore, we are currently looking into the effects of RAGE deletion in additional models of auto-antibody-mediated immune disease. Disclosure of Interest: None declared